Determination of incidence of pectoralis minor muscle shortening and its effective stretching along with conventional therapy in adhesive capsulitis. - G. YATHEENDRA KUMAR,; SUDHAKAR.S,; K. NASREEN SULTANA,; SIVA JYOTHI .N, (International Journal of Pharma and Bio Sciences, 2017)
The objective of this study is to determine the incidence of pectoralis minor muscle shortening and its effective stretching in conjuction with a conventional therapy in adhesive capsulitis.50 subjects underwent the pectoralis minor muscle length test using Pectoralis Minor Muscle Index (PMI).PMI is suggested to show a shortened pectoralis minor when it is 7.65 or lower. As a result, out of 50 subjects, 30 were selected to participate in the study.30 subjects fulfilling the inclusion criteria were assigned into 2 groups, control group (n=15) receiving conventional therapy and experimental group (n=15) receiving pectoralis minor Gross Stretch along with conventional therapy. There is large and medium effect size showing clinically significant differences in means of VAS, ROM, SPADI and PMI between the groups. The present study concludes that implementation of pectoralis minor Gross Stretch in conjuction with conventional treatment in the treatment of Adhesive Capsulitis is beneficial.